An Audit of the Haemodynamic and Emergence Characteristics of Single-Shot 'ketofol'. Issue 4 (July 2015) - Grace, R. F.; Tang, W.; Namel, E.
'Ketofol', the single-syringe combination of ketamine and propofol (50 mg of ketamine and 90 mg of propofol in a 10 ml syringe) is becoming increasingly popular for short procedures, progressively replacing the more traditional use of ketamine and diazepam in some settings. This audit examined the haemodynamic, emergence and other characteristics of ketofol administration in 42, otherwise fit, women undergoing bilateral post-partum tubal ligation at Vila Central Hospital in Vanuatu. The combination of ketamine and propofol had no clinically important adverse haemodynamic effects. Wake-up from ketofol was favourable, with low rates of nausea and minimal emergence delirium. However, 43% of patients required airway support. For short procedures such as post-partum tubal ligation in fit patients, ketofol appears to have minimal adverse haemodynamic effects and favourable emergence characteristics.